2014
DOI: 10.1158/2326-6066.cir-13-0207
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Inhibition Prior to Hypofractionated Radiation Enhances Efficacy in Preclinical Models

Abstract: The immune infiltrate in colorectal cancer has been correlated with outcome, such that individuals with higher infiltrations of T cells have increased survival independent of the disease stage. For patients with lower immune infiltrates, overall survival is limited. Because the patients with colorectal cancer studied have received conventional cancer therapies, these data may indicate that the pretreatment tumor environment increases the efficacy of treatments such as chemotherapy, surgery, and radiotherapy. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…TGFβ also inhibits the cytotoxicity of CD8 T cells 47 . Thus, inhibiting TGFβ has the potential to disrupt the immunosuppressive TME on multiple fronts, and preclinical studies have shown improved tumor responses to radiation when combined with TGFβ inhibition 48, 49…”
Section: Immune System and Cancermentioning
confidence: 99%
“…TGFβ also inhibits the cytotoxicity of CD8 T cells 47 . Thus, inhibiting TGFβ has the potential to disrupt the immunosuppressive TME on multiple fronts, and preclinical studies have shown improved tumor responses to radiation when combined with TGFβ inhibition 48, 49…”
Section: Immune System and Cancermentioning
confidence: 99%
“…Extensive efforts to improve the clinical management of patients with colorectal cancer have been made, but approved treatments only offer limited survival benefit. Therefore, alternative therapeutic strategies such as radioimmunotherapy need to be explored with preclinical animal models (16, 17). It has already become evident that the immune infiltrate including type, density, and location of immune cells within human colorectal tumors predict clinical outcome such that individuals with higher infiltrations of T cells have increased survival independent of the disease stage (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, TGF-beta blockade in this model was unable to mediate a significant anti-tumor effect, either alone, combined with RT or with LM-based vaccination. Those data are perhaps somewhat contradictory to recent studies demonstrating that blocking TGF-β prior to hypofractionated radiation enhances preclinical responses (35), and additional work will be required to determine whether these differences reflect the use of different TGF-β blocking agents, the location of the tumor, or the cancer model under study. While our studies focused on microglia and antigen-presenting cells in the tumor draining lymph nodes and spleen, it is clear that tolerance to tumor antigens is mediated by a number of additional myeloid cell types, particularly myeloid derived suppressor cells (MDSC) (31).…”
Section: Discussionmentioning
confidence: 63%